(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The modern state have been studied of the natural reserves of raw materials St. John’s wort plant Hypericum perforatum L. (H. Komarovii Gorschk.) at the areas of Zhol Kungoy, Kichi Taldyk, Characha , Kosh Zhylga. Plant communities in which H. Perforatum is dominant and subdominant. Biological and exploitable reserves of raw materials of H. Perforatum have been determined